Analytical Hierarchal Process (AHP) Approach in Product Selection (Cell Phone) - THUMMALA, VENKATAMUNI (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
Abstract: Many consumers purchase multi-functional products according to their individual preferences. Consumers are normally aware of their basic needs, but often have no idea of product types, functions, usage and terminology showing important information. This paper presents a method to translate customer needs into applicable alternative Combinations for the products available. In this paper, the theory of the Analytic Hierarchy Process (AHP) is utilized to evaluate the importance of customer needs, which are generally rated and described by qualitative expressions. By asking questions and obtaining preferences, decision script can determine which of our products best meets our customers' needs. The products are then listed in ranking order, allowing the customers to make the final choice. The Analytical hierarchical process model is employed to establish the relationship between customer needs and alternatives for a multi functional product. Selection of Cell phone model is a case study to demonstrate the work through Microsoft Excel software.